High-Flow Nasal Cannula versus Noninvasive Positive Pressure Ventilation in Patients with Heart Failure after Extubation: An Observational Cohort Study - Che-Jung Chang; Ling-Ling Chiang; Kuan-Yuan Chen; Po-Hao Feng; Chien-Ling Su; Han-Shui Hsu (Canadian Respiratory Journal)
Noninvasive positive pressure ventilation (NPPV) has been widely applied in patients with high-risk extubation failure, including heart failure. High-flow nasal cannula (HFNC) has been demonstrated to benefit patients with heart failure by reducing cardiac preload. This study aimed to compare the effectiveness of HFNC to NPPV for preventing extubation failure in patients with heart failure. This 3-year retrospective and single-center cohort study included patients with heart failure with left ventricular ejection fraction <50% who received prophylactic HFNC or NPPV after scheduled extubation from January 2015 to January 2018 from a medical center with four adult intensive care units. Demographics, comorbidities, diagnosis, and weaning status were collected. The primary outcome was treatment failure within 72 hours after extubation, which was defined as escalation to NPPV or reintubation in the HFNC group and was defined as requiring reintubation in the NPPV group. Secondary outcomes were reintubation within 72 hours, reintubation, duration of stay, and mortality during the intensive care unit and hospital stay. Of the 104 patients analyzed, characteristics of 58 patients in the HFNC group and 46 patients in the NPPV group were compared. The treatment failure within 72 hours in the two groups was not significantly different (25.9% vs 13%, p=0.106). Hypoxemic respiratory failure related treatment failure was significantly higher in the HFNC group. Prophylactic HFNC as first-line therapy had a comparable rate of reintubation within 72 hours to the prophylactic NPPV alone (17.2% vs 13%, p=0.556). Other secondary outcomes were similar between the two groups. Among patients with heart failure, HFNC was not inferior to NPPV for preventing extubation failure and reintubation. However, in case of an impending respiratory failure, selective patients may benefit from rescue NPPV.